Water deficits and organic fertilizer doses in the development of young andiroba plants (Research, Society and Development, 2021)
Andiroba has great socioeconomic importance for the Amazon. Thus, the objective was to evaluate the use of organic fertilization and watering shift in the development of andiroba plants. The experiment was conducted in a greenhouse at the UFRA Campus in Capitão Poço - PA. The following proportions of organic fertilizers were analyzed: a) 100% soil, b) 90% soil + 10% organic fertilizer, c) 80% soil + 20% organic fertilizer and d) 70% soil + 30% of organic fertilizer. In addition, the seedlings were subjected to the following water regimes: a) daily, b) every 5 days and c) every 10 days. Plant height (HP), length (CC) and stem diameter (DC), number of leaves (NF), leaf transpiration (E), stomatal resistance (Rs), root (MSR), stem (MSC), leaf (MSF), shoot (MSPA) and total dry matter (MST), MSR/MSPA ratio and biomass allocations in the different vegetative parts were evaluated. The design used was randomized blocks, in a 4 x 3 x 5 factorial scheme (proportions of organic fertilizer, water regimes and times) for AP, CC, DC and NF and in a 4 x 3 factorial scheme for the others variables. Means were submitted to Tukey's test (p